The Influence of the Work Environment and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at the BPJS Kisaran Branch and Padang Sidimpuan Branch - Amri Irwansyah; Mesra B (Lafadz Jaya Publisher, 2024)
This research aims to see the effect of job training and work motivation on employee performance with job satisfaction as an intervening variable at the Bpjs Ketenagakerjaan offices in Kisaran and Padang Sidimpuan branches, using quantitative techniques as the type of research. The population used was 76 employees and the sample used was also 76 employees. because it uses saturated samples as a sampling technique. The research data source used is a primary data source and the data collection used is a questionnaire. This research method uses phat analysis and smart PLS as measuring tools. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Employee Performance with original sample values 0.756 and p value 0.000 <0.05. Work Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.638 and ap value of 0.040 <0.05. Work Motivation has a positive and insignificant effect on Employee Performance with an original sample value of 0.067 and ap value of 0.067 > 0.05. Job Training has a positive and significant effect on Job Satisfaction with an original sample value of 0.317 and ap value of 0.000 <0.05. Job Training has a positive and insignificant effect with an original sample value of 0.130 and ap value of 0.130 > 0.05. Work Motivation has a positive and significant indirect effect on Employee Performance through Job Satisfaction with an original sample value of 0.482 and ap value of 0.000. Job Training has a positive and significant indirect effect on Employee Performance with an original sample value of 0.239 and ap value of 0.000.